Introduction Strategies for English Extracurricular Masterpieces - Ndabeni, Mbongi (Journal of Educational Research and Policies, 2024)
Comprehension Passages: A Guide for English Teachers provides a comprehensive overview of strategies and methodologies to enhance reading comprehension among English language learners. It begins by emphasising the crucial role of reading comprehension in language learning and identifying the common challenges students face while dealing with comprehension passages. The article outlines the cognitive processes involved in reading comprehension, including the decoding of text and the integration of new information with existing knowledge, and discusses the common obstacles students encounter. Key teaching strategies for reading comprehension are explored in detail. These include pre - reading strategies that activate prior knowledge and set purposes for reading, during - reading strategies that maintain engagement and foster understanding, and post - reading strategies that reinforce learning and evaluate comprehension. The integration of technology and multimedia in reading lessons is highlighted, emphasising the use of digital tools and interactive content to cater to diverse learning styles and preferences. Additionally, the article discusses the importance of adapting teaching methods to accommodate various learners, underscoring the need for understanding different learning styles in the context of reading comprehension. It also delves into the role of assessment and feedback in reading education, outlining effective methods for assessing reading comprehension skills and providing constructive feedback to improve student performance. Overall, the article serves as a practical guide for English teachers, offering insights and strategies to effectively navigate the complexities of teaching reading comprehension. It aims to equip educators with the tools necessary to enhance their students' reading skills, thereby fostering a deeper understanding and appreciation of the written word.